Iron overload reduces synthesis and elimination of bile acids in rat liver - Prasnicka, Alena; Lastuvkova, Hana; Alaei Faradonbeh, Fatemeh; Cermanova, Jolana; Hroch, Milos; Mokry, Jaroslav; Dolezelova, Eva; Pavek, Petr; Zizalova, Katerina; Vitek, Libor; Nachtigal, Petr; Micuda, Stanislav (Scientific reports, 2019)
Excessive iron accumulation in the liver, which accompanies certain genetic or metabolic diseases, impairs bile acids (BA) synthesis, but the influence of iron on the complex process of BA homeostasis is unknown. Thus, we evaluated the effect of iron overload (IO) on BA turnover in rats. Compared with control rats, IO (8 intraperitoneal doses of 100 mg/kg every other day) significantly decreased bile flow as a consequence of decreased biliary BA secretion. This decrease was associated with reduced expression of Cyp7a1, the rate limiting enzyme in the conversion of cholesterol to BA, and decreased expression of Bsep, the transporter responsible for BA efflux into bile. However, IO did not change net BA content in faeces in response to increased intestinal conversion of BA into hyodeoxycholic acid. In addition, IO increased plasma cholesterol concentrations, which corresponded with reduced Cyp7a1 expression and increased expression of Hmgcr, the rate-limiting enzyme in de novo cholesterol synthesis. In summary, this study describes the mechanisms impairing synthesis, biliary secretion and intestinal processing of BA during IO. Altered elimination pathways for BA and cholesterol may interfere with the pathophysiology of liver damage accompanying liver diseases with excessive iron deposition.
Keywords: játra; Oxidative Stress; Cholesterol; Iron Overload; Bile Acids and Salts; exprese genu; oxidační stres; messenger RNA; Gene Expression; cholesterol; žlučové kyseliny a soli; krysa rodu Rattus; Biomarkers; zvířata; RNA, Messenger; biologické markery; Liver; Rats; Animals; přetížení železem; Disease Models, Animal; modely nemocí na zvířatech